PFI: is Malaysia ready? - Abdul Rashid, Khairuddin (2009)
In 2006 Malaysia introduced PFI. This paper provides an update on the Malaysian PFls and reports on the findings of a survey to identify competencies and to ascertain whether key players of the Malaysian Construction Industry possess those competencies in the provision of PFI services. In terms of an update on the current state of the Malaysian PFls, the findings show that there are three types of PFI namely the Universal Approach PFI; PFI for the Ministry of Home Affairs (KDN); and PFI under the Ninth Malaysia Plan. The Universal Approach PFI is yet to be implemented and procedure for implementation is still being formulated. The PFI for KDN and PFI under the Ninth Malaysia Plan are not PFls in the true sense. In relation to the survey, the findings indicated most Quantity Surveyors, Architects, Financiers, Engineers and Contractors do possess the general understanding of PFI and thirty-one key PFI competencies have been identified. In addition, the survey identified that constraints exist in the vailability of Malaysians that can provide expert PFI services.